2013
DOI: 10.1186/2190-4715-25-33
|View full text |Cite
|
Sign up to set email alerts
|

Rat feeding studies with genetically modified maize - a comparative evaluation of applied methods and risk assessment standards

Abstract: A 2-year rat feeding study with genetically modified NK603 maize sparked an international scientific and public debate as well as policy responses by the European Commission. The European Food Safety Authority (EFSA) evaluated the study as defective based on conceptual and methodological shortcomings by retroactive application of the recommendations of its recent guidance on 90-day feeding studies. Our comparative analysis of the three relevant NK603 publications, including a 90-day feeding study of Monsanto, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…As we have described in previous commentaries, also published in Meyer and Hilbeck (2013) and, again, are repeating here, the 'comparative analysis' includes a hidden normative element and decision-making step at the technical level and intermingles it with statistical analyses solely on the quantitative nature of a data set that has been designed to contain a lot of unrelated 'noise', additionally, making the detection of differences that can be assigned to the GM component almost impossible -by design. This approach is scientifically questionable -certainly biased -and the normative dimensions are undeclared.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…As we have described in previous commentaries, also published in Meyer and Hilbeck (2013) and, again, are repeating here, the 'comparative analysis' includes a hidden normative element and decision-making step at the technical level and intermingles it with statistical analyses solely on the quantitative nature of a data set that has been designed to contain a lot of unrelated 'noise', additionally, making the detection of differences that can be assigned to the GM component almost impossible -by design. This approach is scientifically questionable -certainly biased -and the normative dimensions are undeclared.…”
Section: Discussionmentioning
confidence: 90%
“…While over the past years, no norms, standards, and scientific criteria for the concept of familiarity and its core instrument of reference controls were developed, it is still at the discretion of applicants and authorities if and how to use the respective test results." (Meyer and Hilbeck 2013) Interestingly, EFSA again fails to determine scientifically sound selection criteria for choosing the non-GM reference varieties, which are the basis of the concept of 'familiarity'. To establish a 'natural variation' that could contribute somehow to EU environmental and health risk assessment the non-GM reference varieties should have relevance in the food and feed supply of the EU.…”
Section: Netherlandsmentioning
confidence: 99%
“…Meyer and Hilbeck [21] have published an in-depth comparative analysis that included both Séralini et al [2] and Hammond, et al [4], which comes to the same conclusion.…”
Section: Imposed Retractionmentioning
confidence: 86%
“…These are not synonymous. Furthermore, as Schubert [19], Meyer and Hilbeck [21] and others have pointed out, if Hayes' reading of this recommendation were applied uniformly, most of the scientific literature would have to be retracted. It is the nature of research results that they are inconclusive.…”
Section: Imposed Retractionmentioning
confidence: 99%
“…Heinemann [4] defended Seralini et al's paper long before it was retracted, and Meyer and Hillbeck [7] demonstrated how the criticism by the European Food Safety Authority (EFSA) suffered from double standards. Following these, I question here whether there exists sufficient substantive evidence given by critics (other than EFSA) to deny the validity of Seralini et al's findings.…”
Section: Introductionmentioning
confidence: 99%